Pengaruh Person Job Fit dan Person Organization Fit Terhadap Organizational Citizenship Behavior dan Kinerja Karyawan Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin - Alfani, Muhammad; Hadini, Muhammad (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
Research done on employees of the University of Islamic Kalimantan Muhammad Arsyad Al Banjari Banjarmasin about person job fit (PJFit) and the person organization fit (POFit) against organization citizenship behavior (OCB) and The employee performance.From a population of 105 employees the University of Islamic Kalimantan Muhammad Arsyad Al Banjari, Banjarmasin, and by using the formula the census, then spread the now to as many as 105 people sample respondents.By using the software AMOS version 20.0 SEM model equations and use, so that research results obtained; The perception of the person job fit has no effect to the OCB and has no effect to the performance of employees.But the perception of the person job fit has effect to OCB and to on employee performance, if applied to the assumption that it is implemented properly in the process of recruitment of the employees in the form of the application of the jobs analysis, of the job description, and the job specification, as well as the assessment of the work or Jobs Evaluation.Furthermore the perception person organization fit significantly to effect the OCB and employee performance.Perception OCB significantly influential on performance of employees